AB1179 Musculoskeletal pattern of 18f-fdg uptake in patients with polymyalgia rheumatica. (12th June 2018) - Prieto-Peña, D.; Loricera, J.; Martínez-Rodríguez, I.; Banzo, J.; Calderón-Goercke, M.; Calvo-Río, V.; González-Vela, C.; González-Gay, M.; Hernández, J.; Blanco, R.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory rheumatic disease of the elderly whose diagnosis is usually based on clinical and ultrasound findings. Recently, 18 F-FDG PET/CT has been proposed as a promising one-step tool for assessing extent and severity of PMR. However, the pattern of 18 F-FDG uptake in PMR is not well established and there is a lack of imaging guidelines. Objectives: Our aim was to describe the musculoskeletal pattern of 18 F-FDG uptake in PMR patients and assess if there were any differences between classic and atypical PMR. Methods: Retrospective study of 75 patients with PMR and their respective PET/CT scans from a referral centre. We considered two groups: a) Classic PMR: patients who fulfilled the 2012 EULAR/ACR criteria; and b) Atypical PMR: patients with symptoms resembling PMR but did not fulfil the 2012 EULAR/ACR criteria. Distributions of categorical variables were compared by Pearson Chi2 or Fisher exact test as appropriate. Results: We evaluated 75 patients (27 men and 48 women) with a mean age ±SD of 68.2±10.7 years. A PET/CT was performed in all of them. Forty-two (56%) patients classic PMR and 33 (44%) atypical PMR. FDG-PET uptake was observed in the following musculoskeletal regions: in shoulders (n=45), sternoclavicular joints (n=33), hips (n=32), cervical interspinous bursae (n=8), lumbar interspinous bursae (n=29), pubic symphysis (n=4), subtrochanteric bursae (n=20), ischial tuberosities (n=19) and knees (n=33). The comparative study between both groups is shown in the TABLE, without observing any statistical significance. Conclusions: In patients with PMR, 18 F-FDG uptake seems to be more frequent in shoulders, sternoclavicular joints, hips and knees. In addition, 18 FDG uptake can be also detected in lumbar interspinous bursae and less frequently in subtrochanteric bursae, ischial tuberosities, cervical interspinous bursae and pubic symphysis. No differences between classic and atypical PMR patients were seen. Disclosure of Interest: None declared